Comparison of Alum and Coal-Based Activated Carbon for the Treatment of Raw Water - Subroto Subroto; Muhammad Said; Eddy Ibrahim; Poedji Loekitowati Hariani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2025)
The availability of clean water is an essential element for supporting the life cycle and sustainable development. The efficiency of providing raw water sources is an important factor for adequate water quantity and quality. This study examines the effectiveness of alum compared with coal-based activated carbon in the removal of Fe, Mn, and turbidity in raw water from the Lematang River, Muara Enim Regency. Activated carbon in this study was produced using a KOH activator with varying activation temperatures (700 °C, 800 °C, and 900 °C). The research results showed that the quality of the third activated carbon met the active carbon quality standards (moisture, ash content, Methylene blue dye and iodine adsorption capacity), but the activated carbon with activation at a temperature of 800 °C had the largest surface area. Activated carbon was proven more effective in reducing Fe and Mn concentrations than alum, while alum was superior in reducing turbidity. After three cycles of activated carbon regeneration, the reduction in Fe and Mn remained below 5%. These results show that activated carbon is a cost-effective and eco-friendly option for raw water treatment.Keywords: Coal, activated carbon, alum, raw water, regeneration